2021
DOI: 10.21608/jpp.2021.157370
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis for some Economic Traits in Sunflower (Helianthus annuus L.).

Abstract: Seven sunflower cytoplasmic male sterile (CMS lines) and three Rf-restorer (tester lines) were used to obtain 21 F1 hybrids according to line x tester mating design. All the 21 F1 hybrids, 7 lines, and three testers were evaluated at Sakha Agricultural Research Station, Kafer El-Sheikh Governorate during 2017 season. The results showed highly significant differences among the genotypes for all the studied traits. The major role of dominant genes was found because the degree of dominance was greater than unity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…In the current study, the enhancement of growth parameters of wheat plants by the spraying of commercial or fresh algal extracts may be due to the presence of cytokinin's, minerals, and various nutrients in the prepared extracts. These ingredients are known to improve the growth and increase cell division and cell enlargement [36,37]. Compatible with the obtained results, Mansori et al [38] showed that the growth and yield of Cajanus cajan (L.) Millsp., Vigna sinensis L., and Phaseolus vulgaris L. cultivated under water stress were improved by the foliar spray of an algal extract.…”
Section: Effect Of the Foliar Spray Of Aqueous Algal Extracts On The ...mentioning
confidence: 79%
“…In the current study, the enhancement of growth parameters of wheat plants by the spraying of commercial or fresh algal extracts may be due to the presence of cytokinin's, minerals, and various nutrients in the prepared extracts. These ingredients are known to improve the growth and increase cell division and cell enlargement [36,37]. Compatible with the obtained results, Mansori et al [38] showed that the growth and yield of Cajanus cajan (L.) Millsp., Vigna sinensis L., and Phaseolus vulgaris L. cultivated under water stress were improved by the foliar spray of an algal extract.…”
Section: Effect Of the Foliar Spray Of Aqueous Algal Extracts On The ...mentioning
confidence: 79%